Synthesis and wound healing of alternating block polyurethanes based on poly(lactic acid) (PLA) and poly(ethylene glycol) (PEG). Issue 5 (5th April 2016) - Li, Linjing; Liu, Xiangyu; Niu, Yuqing; Ye, Jianfu; Huang, Shuiwen; Liu, Chao; Xu, Kaitian
Abstract: Alternating block polyurethanes (abbreviated as PULA‐ alt ‐PEG) and random block polyurethanes (abbreviated as PULA‐ ran ‐PEG) based on biodegradable poly(lactic acid) (PLA) and poly(ethylene glycol) (PEG) were prepared. Results showed that alternating block polyurethane gives higher crystal degree, higher mechanical properties, more patterned and rougher surface than the random counterpart, due to the regular and controlled structure. Water absorptions of the polyurethanes were in the range of 620 to 780%. Cytocompatibility of the amphiphilic block polyurethanes (PU) (water static angle 41.4°–61.8°) was assessed by CCK‐8 assay using human embryonic kidney (HEK293) cells. Wound healing evaluation of the PU foam scaffolds was carried out by full‐thickness SD rat model experiment, with medical gauze as control. It was found that the skin of rat in PU groups was fully covered with new epithelium without any significant adverse reactions and PU dressings give much rapid and better healing than medical gauze. Histological examination revealed that PU dressings suppress the infiltration of inflammatory cells and accelerate fibroblast proliferation. It was also demonstrated that PULA‐ alt ‐PEG exhibits obvious better healing effect than PULA‐ ran ‐PEG does. This study has demonstrated that without further modification, plain alternating block polyurethane scaffold would help wound recovery efficiently. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 105B: 1200–1209, 2017.